IMPROVING MANAGERIAL BEHAVIOR UNDERSTANDING THROUGH THE IMPLEMENTATION OF BEHAVIORAL ACCOUNTING IN MSMES: A CASE STUDY ON GINZA BUSSINESS - Rita J D Atarwaman; Syantal Mustamu; Claudya Ifentri; Jumiati Lahadasi; Johan Daud Banawi; Zuleyka Tahera Marasabessy; Pieter Rumawatine (PT. Jurnal Center Indonesia Publisher, 2026)
Micro Small and Medium Enterprises (MSMEs) play a vital role in the economy, yet they still face numerous challenges in managerial behavior and financial management. One relevant approach to addressing these issues is the application off behavioral accounting which emphasizes the relationship between accounting information and decision-making behavior. This community service activity aims to improve the understanding of the behavior of MSMEs in Ginza. The method used included an initil survey, managerial behavior training, a behavior accounting, workshop,and mentoring on simple financial record keeping. The results indicate and increased understanding of MSMEs regarding the importance of financial record keeping, cost control, and the division of responsibilities in business management. The application off behavior accounting has a positive impact on changing manajerial behavior and increasing business accountability.